Force funding of infrastructure: off-budget and off-key? - Mukhopadhyay, Partha (2004)
It is easy to force-fund infrastructure by persuading the banks and the RBI to lend money, but this is only likely to result in a fragile banking system. The gains will be greater if the projects are first made viable. Investors will channel resources into infrastructure once a market has been created, regulation put in place, and tariff reform implemented. - Reproduced.
Keywords: Banks - India; Banks